2020
DOI: 10.3389/fonc.2019.01536
|View full text |Cite
|
Sign up to set email alerts
|

Is Lactate an Oncometabolite? Evidence Supporting a Role for Lactate in the Regulation of Transcriptional Activity of Cancer-Related Genes in MCF7 Breast Cancer Cells

Abstract: Lactate is a ubiquitous molecule in cancer. In this exploratory study, our aim was to test the hypothesis that lactate could function as an oncometabolite by evaluating whether lactate exposure modifies the expression of oncogenes, or genes encoding transcription factors, cell division, and cell proliferation in MCF7 cells, a human breast cancer cell line. Gene transcription was compared between MCF7 cells incubated in (a) glucose/glutamine-free media (control), (b) glucose-containing media to stimulate endoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 82 publications
(101 reference statements)
4
72
0
2
Order By: Relevance
“…Lactate has been shown to alter the transcriptional activity of several key oncogenes, and increased carcinogenesis signaling due to augmented lactate production can serve as one essential purpose of the Warburg effect 31 . Lactate metabolism is particularly relevant for not only the metabolic equilibrium between hypoxic (lactate-generating) and normoxic (lactate-importing) cancer cells 32 but also the polarization of TAMs by hypoxic cancer cells toward a poorly glycolytic M2-like profile 33 - 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Lactate has been shown to alter the transcriptional activity of several key oncogenes, and increased carcinogenesis signaling due to augmented lactate production can serve as one essential purpose of the Warburg effect 31 . Lactate metabolism is particularly relevant for not only the metabolic equilibrium between hypoxic (lactate-generating) and normoxic (lactate-importing) cancer cells 32 but also the polarization of TAMs by hypoxic cancer cells toward a poorly glycolytic M2-like profile 33 - 35 .…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study, our group has previously reported in MCF7 that high glucose induced the Warburg effect, as characterized by an increase in lactate secretion, together with increased lactate transporters and reduced oxidative phosphorylation [ 32 ]. Endogenous, glucose-derived lactate may increase transcription of oncogenes and tumour suppressors such as BRCA1 [ 63 ] and may be preferred over glucose by tumour cells for oxidative metabolism [ 64 ]. While these possible independent effects may not be completely accounted for in the current study, spent media was changed every 24 h to avoid accumulation of metabolism by-products such as lactate [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the importance of maintaining homeostasis in physiology, the deleterious effect of prolonged, continuous La − accumulation, as occurs in cancer by comparison to the intermittent La − stimulus during exercise, deserves further exploration (San‐Millan et al . 2019).…”
Section: Rationale and Outlinementioning
confidence: 99%